Influence of Humic Acid on Interaction of Ammonium and Potassium Ions on Clay Minerals - ZHANG, Wen-Zhao; CHEN, Xiao-Qin; ZHOU, Jian-Min; LIU, Dai-Huan; WANG, Huo-Yan; DU, Chang-Wen (Pedosphere, 2013)
Interaction of ammonium （NH4＋） and potassium （K＋） is typical in field soils. However, the effects of organic matter on interaction of NH4＋ and K＋ have not been thoroughly investigated. In this study, we examined the changes in major physicochemical properties of three clay minerals （kaolinite, illite, and montmorillonite） after humic acid （HA） coating and evaluated the influences of these changes on the interaction of NH4＋ and K＋ on clay minerals using batch experiments. After HA coating, the cation exchange capacity （CEC） and specific surface area （SSA） of montmorillonite decreased significantly, while little decrease in CEC and SSA occurred in illite and only a slight increase in CEC was found in kaolinite. Humic acid coating significantly increased cation adsorption and preference for NH4＋, and this effect was more obvious on clay minerals with a lower CEC. Results of Fourier transform infrared spectrometry analysis showed that HA coating promoted the formation of H-bonds between the adsorbed NH4＋ and the organo-mineral complexes. HA coating increased cation fixation capacity on montmorillonite and kaolinite, but the opposite occurred on illite. In addition, HA coating increased the competitiveness of NH4＋ on fixation sites. These results showed that HA coating affected both the nature of clay mineral surfaces and the reactions of NH4＋ and K＋ with clay minerals, which might influence the availability of nutrient cations to plants in field soils amended with organic matter.